Amino Acids: Metabolism, Functions, and Their Role in Health and Disease Management - Rand Thair Abdul-kader (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Abstract. Amino acids are indispensable components of human metabolism, playing essential roles in proteinsynthesis, energy production, and cellular regulation. Branched-chain amino acids (BCAAs)-leucine, isoleucine,and valine—are particularly significant due to their involvement in muscle repair, metabolic signaling, andinsulin sensitivity. While BCAAs are vital under normal physiological conditions, multiple studies have shownthat elevated plasma BCAA levels are linked to insulin resistance, obesity, and type 2 diabetes. This associationhas led researchers to investigate whether these elevations are a cause or consequence of metabolicdysfunction. Recent findings have revealed that impaired BCAA catabolism in tissues such as adipose and livercontributes to their accumulation in circulation. If skeletal muscle becomes insulin resistant, it may shift BCAAmetabolism further, exacerbating the imbalance. Moreover, the modulation of specific enzymes and transportershas been proposed as a therapeutic avenue to mimic the beneficial effects of dietary protein restriction.Although several mechanisms have been proposed, including mTOR activation, fatty acid oxidationinterference, and altered neurotransmitter synthesis, no single pathway fully explains BCAA-induced metabolicdisturbances. Therefore, a comprehensive understanding of amino acid metabolism is crucial, particularly ifdietary and pharmacological interventions are to be optimized for preventing or treating age-related andmetabolic diseases.